The Influence of 3D Printing Parameters on Adhesion between Polylactic Acid (PLA) and Thermoplastic Polyurethane (TPU) - Emila Brancewicz-Steinmetz (MDPI AG, 2021)
A 3D printer in FDM technology allows printing with two nozzles, which creates an opportunity to produce multi-material elements. Printing from two materials requires special consideration of the interface zone generated between their geometrical boundaries. This article aims to present the possibility of printing with PLA and TPU using commercially available filaments and software to obtain the best possible bond strength between two different polymers with respect to printing parameters, surface pattern (due to the material contact surface’s roughness), and the order of layer application. The interaction at the interface of two surfaces of two different filaments (PLA-TPU and TPU-PLA) and six combinations of patterns were tested by printing seven replicas for each. A total of 12 combinations were obtained. By analyzing pairs of samples (the same patterns, different order of materials), the results for the TPU/PLA samples were better or very close to the results for PLA/TPU. The best variants of pattern combinations were distinguished. Well-chosen printing parameters can prevent a drop in parts efficiency compared to component materials (depending on the materials combination).